2009
DOI: 10.1002/mds.22463
|View full text |Cite
|
Sign up to set email alerts
|

Motor‐related circuit dysfunction in MSA‐P: Usefulness of combined whole‐brain imaging analysis

Abstract: The aim of this study was to evaluate in vivo changes in the brain's macro- and microstructure (notably in the motor system) in the parkinsonian variant of multiple system atrophy (MSA-P) and in Parkinson's disease (PD) and to characterize the cerebral anatomical differences between the two conditions. We used a combination of voxel-based morphometry (VBM) and whole-brain, voxel-based diffusion tensor imaging analysis (VB-DTI). Forty-seven right-handed subjects (14 MSA-P patients, 19 PD patients, and 14 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 49 publications
6
26
0
Order By: Relevance
“…This is particularly obvious when images of patients with symptoms dominant on the left side are flipped horizontally to match those of patients with right-sided clinical dominance. This finding is congruent with prior studies reporting changes in the left cerebral hemisphere and the right cerebellum in MSAp [23,33]. Congruently, our results suggest morphological alterations on the cerebral hemisphere contralateral to the dominating clinical symptoms.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is particularly obvious when images of patients with symptoms dominant on the left side are flipped horizontally to match those of patients with right-sided clinical dominance. This finding is congruent with prior studies reporting changes in the left cerebral hemisphere and the right cerebellum in MSAp [23,33]. Congruently, our results suggest morphological alterations on the cerebral hemisphere contralateral to the dominating clinical symptoms.…”
Section: Discussionsupporting
confidence: 83%
“…In MSAp there is evidence for atrophy both of the putamen itself and the periputaminal internal capsule [8,9,23], which may occur in parallel. Furthermore, degeneration of the corticospinal tract would be concordant with the finding of decreased FA of the primary motor cortex [33], implying that MSAp affects pyramidal motor pathways earlier and stronger than PD. While VBM analysis of our data did not demonstrate significant macroscopic group-specific atrophy, this aspect should be evaluated in a larger sample.…”
Section: Discussionmentioning
confidence: 71%
“…Four of these focused on ROIs in the middle cerebellar peduncles, detecting reduced FA. 7,33,35,37 Three studies found an increase in MCP diffusivity measures 7,23,38 ; one other VBA study 36 detected no significant diffusivity differences. One study examined the putamen in MSA finding FA reduced and ADC increased 8 ; another found elevated FA.…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36] A few studies found more local reduction of GM in PD, although the regions were inconsistent across the studies. 37,38 In addition, some reports showed no differences between PD and controls. 39,40 Differences in the relative representation of the PIGD and TD subtypes may explain the disparate findings in these earlier reports.…”
Section: Resultsmentioning
confidence: 99%